Native hepatic T1-time as a non-invasive predictor of diastolic dysfunction and a monitoring tool for disease progression and treatment response in patients with pulmonary hypertension - Kremer, Nils; Roller, Fritz C.; Kremer, Sarah; Schäfer, Simon; Kryvenko, Vitalii; Rako, Zvonimir A.; Brito da Rocha, Bruno R.; Yogeswaran, Athiththan; Seeger, Werner; Guth, Stefan; Wiedenroth, Christoph B.; Tello, Khodr; et al. (My University, 2024)
Aims: Hepatic T1-time derived from cardiac magnetic resonance imaging (cMRI) reflects venous congestion and may provide a simple alternative to invasive end-diastolic elastance (Eed) for assessment of right ventricular (RV) diastolic function. We investigated the association of native hepatic T1-time with single-beat Eed and the value of hepatic T1-time for longitudinal monitoring in pulmonary hypertension (PH). Methods and results: We retrospectively enrolled 85 patients with suspected PH (59% female; 78 with PH diagnosed; 7 with PH excluded) who underwent standard right heart catheterization and cMRI within 24 h between 2015 and 2020. Hepatic T1-time showed moderate to strong correlations (rho >0.3, P ≤ 0.002) with pulmonary vascular resistance, native myocardial T1-time, Eed, RV size and function, brain natriuretic peptide (BNP) level, and 6-min walk distance, and a significant association with functional class (Kruskal-Wallis P < 0.001). Eed, myocardial T1-time, and BNP were independently linked to hepatic T1-time in multivariable regression. Hepatic T1-time > 598 ms predicted elevated Eed with 72.9% sensitivity and 82.1% specificity. Hepatic T1-time was superior to Eed in predicting clinical worsening. In 16 patients with follow-up assessments, those with decreasing hepatic T1-time (7 patients) showed significant hemodynamic improvements, whereas those with increasing hepatic T1-time (9 patients) did not. In a second retrospective cohort of 27 patients with chronic thromboembolic PH undergoing balloon pulmonary angioplasty, hepatic T1-time decreased significantly and hemodynamics improved after the procedure. Conclusions: Hepatic T1-time predicts RV diastolic dysfunction and prognosis, and may be useful for monitoring disease progression and treatment response in PH.
Keywords: ddc:610